SPATIAL DISTRIBUTION AND SHOALING BEHAVIOUR OF FISHERY RESOURCES lN THE WATERS OFF WESTERN COAST OF ACEH: PRELIMINARY RESULTS FROM THE POST TSUNAMI EXPEDITION 2OO5 - Wijopriono Wijopriono; Mohamad Natsir; Aril Slotte; Asep Priatna (Research Center for Fisheries, 2006)
Acoustic investigation, which is one of the programmes of the Post Tsunami Expedition, was done in Aceh waters during 24 July to 14 August 2005. Research vessel Bawal Putih I and Baruna Jaya Vlll were used for the survey.